7,445 at UUM to receive scrolls - News Straits, Times (New Straits Times, 2013)
ALOR STAR: Universiti Utara Malaysia(UUM) will hold its 26th convocation at Dewan Muadzam Shah next Saturday.The fourday event will see 7,445 students graduating with diplomas and degrees.Of the number, 47 students will receive diplomas, 5,803 will receive their degrees and 1,595 postgraduate degrees to be presented in eight sessions.The university will bestow an honorary doctorate on a panel member of the Kelantan Syariah Appeal Court, Tun Ahmad Fairuz Sheikh Abdul Halim.